2007
DOI: 10.2174/157016207781023992
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1-Discordant Couples in Sub-Saharan Africa: Explanations and Implications for High Rates of Discordancy

Abstract: In sub-Saharan Africa, approximately 1 in 2 HIV-1-infected persons living in a couple have a serodiscordant partner. Recent data suggest a large proportion of new HIV-1 infections in mature epidemics occur within discordant couples, making discordancy a major contributor to the spread of HIV/AIDS in Africa. What accounts for high rates of HIV-1 discordance and why some individuals remain uninfected despite repeated sexual exposure to HIV-1 is unknown. Studying HIV-1-discordant couples may contribute to underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 89 publications
1
71
1
Order By: Relevance
“…This may be due to the relatively higher frequency of sex in newer relationships [21, 22]. Additionally, partners who stay negative after longer periods of time in a serodiscordant relationship may have reduced susceptibility of some kind, such as having a protective genetic predisposition or acquired immunity through repeated exposure [23]. In any case, this finding suggests that in Opposites Attract , men in new relationships need to be targeted to ensure that the effect of ART on transmission can be measured.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the relatively higher frequency of sex in newer relationships [21, 22]. Additionally, partners who stay negative after longer periods of time in a serodiscordant relationship may have reduced susceptibility of some kind, such as having a protective genetic predisposition or acquired immunity through repeated exposure [23]. In any case, this finding suggests that in Opposites Attract , men in new relationships need to be targeted to ensure that the effect of ART on transmission can be measured.…”
Section: Discussionmentioning
confidence: 99%
“…Heterosexual transmission among discordant couples in marriage or cohabitation accounts for most of the HIV incidence in this region [2] [36]. In sub-Saharan Africa, in studies where both members of the couple have been tested, rates of serodiscordance range between 1–7% [4, 5, 79] and 10–25% of new HIV infections occur among HIV-discordant couples [10]. In a study of five African countries using Demographic Health Survey (DHS) and AIDS Indicator Survey (AIS) data, de Walque found that among 9,297 infected persons, more than two thirds were in serodiscordant relationships [11].…”
Section: Introductionmentioning
confidence: 99%
“…WHO has issued guidance for couples HIV testing and counseling (CHTC) 4 , which has been used effectively with heterosexual couples in Africa 5-8 . Findings suggest this is a promising strategy for prevention among same-sex male couples 9,10 .…”
Section: Introductionmentioning
confidence: 99%